2022
DOI: 10.18326/ijtihad.v22i1.1-18
|View full text |Cite
|
Sign up to set email alerts
|

Gender Fiqh: Mobilization of Gender-Responsive Movement on Social Media

Abstract: This study aimed to reformulate the ijtihad of gender-responsive fiqh. Such ijtihad model is needed in order to respond to the developments and dynamics of life in the current contemporary era. Moreover, current social reality and condition are often associated with empowerment of and justice for women. Movements and responses toward women’s issues recently has been occurring quite monumentally on social media. Such movements represent a response toward media development, especially on social media platforms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…There are several online classes offered through social media that aim to provide a better understanding of the importance of women's struggle against oppression and discrimination. These online classes demonstrate the possibility of reinterpreting and redefining alternative ijtihad models regarding the position of women in Islamic law (Nurjanah & Nur, 2022). Various community movements and women's groups in campaigning for gender equality through social media seem to involve the discourse of Islamic legal studies.…”
Section: Local Ulama' Thought-style and Its Contribution To The Fiqh ...mentioning
confidence: 97%
“…There are several online classes offered through social media that aim to provide a better understanding of the importance of women's struggle against oppression and discrimination. These online classes demonstrate the possibility of reinterpreting and redefining alternative ijtihad models regarding the position of women in Islamic law (Nurjanah & Nur, 2022). Various community movements and women's groups in campaigning for gender equality through social media seem to involve the discourse of Islamic legal studies.…”
Section: Local Ulama' Thought-style and Its Contribution To The Fiqh ...mentioning
confidence: 97%
“…Some research has suggested that males may be more prone to excessive gaming or gambling-related smartphone apps. At the same time, the female may engage in using social media platforms and ecommerce apps, which can be associated with addictive behaviours (James, O'Malley, & Tunney, 2019;Okiyi et al, 2020;Derevensky et al, 2022;Nurjanah & Nur, 2022).…”
Section: Jip-the Indonesian Journal Of the Social Sciences {107mentioning
confidence: 99%
“…Islamic law also emphasizes that men and women have equal degrees. 35 In reality, during pregnancy, childbirth, and parenting, women are the ones who play the most role and feel the impact. Islam itself has regulated how women actually have reproductive rights to fulfill.…”
Section: Childfree According To Islamic Lawmentioning
confidence: 99%